(3ecGJHGJ aNQ GdOjf Hf ecGfSs - (3GHf ecGfS , YHO GdQMef Hf YHO GdQRGb Hf EHQGgje, aNQ GdOjf CHh GdaQL,J (B794 (3g` s
(3ChdgG (B:s
(3cJH GdUGMH aNQ GdOjf Hf ecGfS dTeS GdOjf GdeJjfi hbO hbY dg eG jhLH Pdc cJH GdbJd hGdbJGd YdjfG s
(3BNQgG (B:s
(3jGHGHi NhP dgG ebdI JZfi GdfOGeG Yf TQGA GdSQGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B310s
(3eUOQ GbJfGA GdCUd (B:s
(3cJHNGfI edi edc (B(2/40) s
Keywords: (3GdCOHs